Braincase With Natural Endocast of a Juvenile Rhinocerotinae From the Late Middle Pleistocene Site of Melpignano (Apulia, Southern Italy) - Iurino, Dawid A.; Conti, Jacopo; Mecozzi, Beniamino; Sardella, Raffaele (Frontiers in Earth Science, 2020)
Cranial remains of juvenile fossil rhinoceroses are rarely described in literature and very few is known about the ontogenetic development of their inner anatomy. In this study, we report the first CT based description of a juvenile braincase and its natural brain endocast of a late Middle Pleistocene Rhinocerotinae from Melpignano (Apulia, Italy). The specimen belongs to an individual about 12–18 months old, representing to date the youngest Pleistocene rhinoceros of Mediterranean Europe documented by neurocranial material. Through digital visualization methods the neurocranium has been restored and the anatomy of both the brain and the paranasal sinuses has been obtained and compared with those of juvenile and adult Pleistocene rhinoceroses. We evidence a different morphological development of the inner cranial anatomy in fossil and extant African species.